LEXICAL THEMES OF SPACE AND TIME (ON THE EXAMPLE OF V.AKSENOV’S NOVEL “IN SEARCH OF THE SAD BABY”) (Proceedings of Southern Federal University. Philology, 2012)
Troshkina T.P.Keywords: personal world perspective, time and space categories, lexical and theme groups.The article is devoted to the problem of the lexical structure of the novel, time and space in the text. The analysis of the text-forming role of the space and time categories allows understanding the inseparable notions of space and time as one of the factors which determine the lexical structure of the novel.